Antioxidant Protection of Donor Packed Red Blood Cells using Mexidol - Gavryuchenkov, D.V.; Fedoseykin, I.V.; Kosachev, V.E.; Shapovalova, V.A.; Dinov, E.N.; Dinova, Y.E.; Nikiforov, I.A.; Merkin, A.G. (Journal of Antioxidant Activity, 2018)
The current research shows the possibility of long-term conservation of the erythrocytes an-tioxidant activity in the process of donor packed red blood cells while introducing mexidol to the hemoconservant glugicir composition.
Keywords: hemoconservants; peroxygenation; glugicir